SILURIAN STRATIGRAPHIC SCALE FOR EAST SIBERIA - Tesakov Yu.I.; Khromykh V.G.; Berger A.Ya.; Predtechenskii N.N. (My University, 1998)
Principles of stratigraphic regionalizing and chronozonal characteristics of global and regional stratigraphic scale for East Siberia are presented. The stratigraphic regionalizing resulted in recognition of five subregions (North Taimyrskii, North Prieniseiskii, Tungusskii, Nyuya-Berezovskii, and Irkutskii) and 15 stratigraphic areas (Middendorf, Norilsk, Turukhansk, Igarka, Kochumdek, Vorogovka, South Taimyr, Ledyanka, Maimecha, Moiero, Morkoka, Vilyui, Nyuya-Berezovka, nim, and Baltura). The global scale is divided into stages and substages are subdivided into 54 global chronozones with indicated first and last occurrence levels of guide fossils, such as graptolites, brachiopods, conodonts, and tabulates. The regional scale of East Siberia is divided into six horizons (Moiero, Khaastyr, Agidy, Khakoma, Tukal, and Postnichnyi) and 13 subhorizons ranging through 54 regional chronozones, whose stratigraphic intervals correspond to those of global chronozones. In East Siberia, the first and last occurrence levels are established for guide species of graptolites, chitinozoans, acritarchs, cephalopods, trilobites, brachiopods, scolecodonts, conodonts, bryozoans, tentaculites, ostracodes, gastropods, crinoids, rugoses, tabulates, stromatoporoids, algae, pelecypods, vertebrates, chiolites, and conularians. Stratotypes are selected for all chronozones (global and regional).
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская